Severe and/or prolonged COVID-19 in hematologic diseases: clinical implications before and during the omicron era - Okamoto, Akinao; Yoshida, Masahiro; Kasahara, Senji; Ara, Takahide; Ozeki, Kazutaka; Morishita, Takanobu; Ikeda, Daisuke; Kanaya, Minoru; Kajiguchi, Tomohiro; Suzuki, Yasuhiro; Kurahashi, Shingo; Horio, Tomohiro; et al. (Frontiers in Oncology, 2025)
BackgroundAlthough the Omicron variant has been reported to reduce COVID-19 severity in the general population, its impact on patients with hematologic malignancies remains uncertain, and epidemiological investigation is warranted.MethodsWe conducted a multicenter retrospective cohort study of 1, 023 patients with hematologic diseases diagnosed with COVID-19 at 22 centers in Japan between January 2020 and January 2023. Outcomes within 60 days after diagnosis including severe and/or prolonged disease, COVID-19–related mortality, and overall survival (OS) were compared between the pre-Omicron and Omicron periods. Multivariable analysis was performed to identify independent adverse prognostic factors.ResultsSevere and/or prolonged disease occurred in 27.5% of patients, COVID-19–related mortality was 6.3%, and OS was 91.4%. Compared with the pre-Omicron period, the Omicron period was associated with significantly lower rates of severe/prolonged disease (26.0% vs. 48.0%, P<0.01) and COVID-19–related mortality (5.0% vs. 15.0%, P<0.01), but no significant difference in OS (92.0% vs. 84.0%, P = 0.62). Age ≥60 years was the strongest predictor of severe/prolonged disease (sHR 3.08, P<0.01) and mortality (HR 8.94, P<0.01). Male sex (sHR 1.38; HR 1.82, both P<0.01) and prior bendamustine exposure (sHR 1.83; HR 1.87, both P<0.01) were also associated with both outcomes, whereas anti-CD38 antibody therapy was linked only to mortality (HR 3.65, P<0.01).ConclusionIn patients with hematologic diseases, the Omicron period was associated with reduced severity and COVID-19–related mortality but no improvement in OS. Older age and prior bendamustine exposure were strongly associated with adverse outcomes, highlighting the need for strict infection prevention and prompt, aggressive COVID-19 management in these high-risk populations.